ASSEMBLING A MULTISENSORY DEVICE FOR MONITORING AND ASSESSING CONCRETE CURING CONDITIONS - Utepov, Ye.B.; Tolkynbayev, T.A.; Aniskin, A.; Akhazhanov, S.B.; Zharassov, Sh.Zh.; Tulebekova, A.S.; Akishev, M.S. (KU Publ., 2022)
The conventional direct and indirect methods to study the mechanical characteristics of concrete are mainly performing discrete measurements, omitting the continuous internal and external phenomena occurring in the concrete body that may significantly affect its strength and quality. This study presents a multisensory device and a method that simultaneously measures and assesses the impact of curing temperature, ambient temperature and relative humidity on the concrete strength. The device was assembled on the basis of Arduino Pro Mini microcontroller connected with various sensors, as well as clock reading and memory modules. The method proposed to assess the impact of different factors on concrete strength is based on strength tests and their confidence curve, monitoring of concrete curing conditions, correlation and weighting techniques. The performance of proposed device and its method was justified experimentally using the concrete cubic specimens of different size. To visualize the specimens monitoring results the color gradations, petal and bar chart representations were used, and taken into account for the future implementation of a software interface for the multisensory device.
Keywords: concrete strength; sensors; continuous phenomena; Arduino; monitoring